Analisis Kejadian Adverse Drug Reaction Obat Anti-Tuberkulosis dengan Faktor Risiko pada Penderita Tuberkulosis Multi-Drug Resistant : Systematic Review - Andili, Agshal Almachzumi; Setiawan, Budhi; Ama, Fuad; Raharjo, Budiono (Calvaria Medical Journal, 2024)
Introduction: Tuberculosis patients must adhere to a six-month uninterrupted course of medication. The DOTS method is crucial in preventing resistance to anti-TB drugs, which can lead to stronger MDR-TB strains resistant to rifampicin and isoniazid. ADRs from these drugs include gastrointestinal disturbances, hepatotoxicity, dermatological and serious neurological disorders, prompting patients to discontinue treatment. Non-adherence can hinder tuberculosis recovery as patients tend to stop treatment. Patient compliance is pivotal in their decision to continue treatment. Therefore, further research is needed to explore the relationship between ADRs to anti-TB drugs and risk factors in active MDR-TB patients. Method: This qualitative study conducted a literature review using databases from 2014 to 2023 and keywords relevant to the study's title. Fifteen relevant journals were identified, comprising 11 international and 4 national journals. Results: The literature review found that the most influential factors in adverse drug reactions to OAT in outpatient MDR-TB patients were treatment history and medication adherence. Regarding individual factors such as age and gender, most journals indicated they are not significant risk factors for MDR-TB. Conclusion: Based on the literature review, it can be concluded that the most dominant factors affecting adverse drug reactions to OAT in outpatient MDR-TB patients are treatment history and medication adherence. As for individual factors like age and gender, nearly all journals indicate they are not significant risk factors for MDR-TB.